2022
DOI: 10.3389/fphar.2022.763909
|View full text |Cite
|
Sign up to set email alerts
|

Inventory Management of Health Commodities in a Tertiary Teaching Hospital in Ethiopia

Abstract: Background: Analyzing purchased health commodities based on their budgetary consumption and importance is crucial for efficient utilization of a hospital’s budget. However, it is rarely seen when hospitals, mostly in developing countries, conduct such kinds of analyses and make an informed decision, including to utilize their limited budget efficiently. Therefore, the purpose of this study was to analyze a 3-year inventory of health commodities (medicines, medical supplies, and laboratory reagents and chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Paul's Hospital Millennium Medical College in Addis-Ababa, Ethiopia, received the results of a drug use profile based on ABC-VEN analysis, which found that 34-39% of the elements fall into category I (AV, AE, AN, CV, BV). This accounted for more than 84-86% of annual hospital spending (Legese et al, 2022). About 56-60% of individuals belonged to category II (BE, CE, BN), which accounted for about 13-15% of their annual expenditures during the academic year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paul's Hospital Millennium Medical College in Addis-Ababa, Ethiopia, received the results of a drug use profile based on ABC-VEN analysis, which found that 34-39% of the elements fall into category I (AV, AE, AN, CV, BV). This accounted for more than 84-86% of annual hospital spending (Legese et al, 2022). About 56-60% of individuals belonged to category II (BE, CE, BN), which accounted for about 13-15% of their annual expenditures during the academic year.…”
Section: Discussionmentioning
confidence: 99%
“…About 56-60% of individuals belonged to category II (BE, CE, BN), which accounted for about 13-15% of their annual expenditures during the academic year. Category III (CN) items accounted for 4%-7% of all pharmaceutical products and less than 1% of spending (Legese et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, the term "ABC analysis" is used ambiguously in the biomedical literature. "ABC analysis" is used for: (i) "Ap-proximate Bayesian Computation" (e.g., 3,4 ), (ii) "Antecedent-Behavior-Consequence", which is a method for analyzing behavior and comes from the field of psychology 5 , and (iii) an inventory categorization method originating in economics, where ABC occasionally stands for "Always Better Control", used in inventory control and management (e.g., [6][7][8][9] ).…”
Section: Methodsmentioning
confidence: 99%
“…However, the term "ABC analysis" is used ambiguously in the biomedical literature. "ABC analysis" is used for: (i) "Ap-proximate Bayesian Computation" (e.g., 3,4 ), (ii) "Antecedent-Behavior-Consequence", which is a method for analyzing behavior and comes from the field of psychology 5 , and (iii) an inventory categorization method originating in economics, where ABC occasionally stands for "Always Better Control", used in inventory control and management (e.g., [6][7][8][9] ).This report refers only to the idea underlying the latter meaning of ABC analysis, i.e., the item or inventory categorization method that aims to identify the most relevant items by dividing a set of non-negative numerical items into subsets "A", "B", and "C" 10 . However, the term "Always Better Control" for "ABC", which was never used by Juran, should not be associated with the present method.…”
mentioning
confidence: 99%
“…However, the term "ABC analysis" is used ambiguously in the biomedical literature. "ABC analysis" is used for: (i) "Approximate Bayesian Computation" (e.g., 3,4 ), (ii) "Antecedent-Behavior-Consequence", which is a method for analyzing behavior and stems from the eld of psychology 5 , and (iii) an inventory categorization method originating in economics where ABC occasionally stands for "Always Better Control" that is used in inventory control and management (e.g., [6][7][8][9] ). This report refers exclusively to the idea underlying the latter meaning of ABC analysis, i.e., the item or inventory categorization method that aims at identifying the most relevant items by dividing a set of nonnegative numerical items into subsets "A", "B" and "C" 10 .…”
Section: Ambiguous Meaning Of the Term "Abc Analysis"mentioning
confidence: 99%